THE IDEOLOGY OF FAR RIGHT POLITICAL PARTIES: SOCIO-ECONOMIC DIMENSION - Гримська, М. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Socio-economic views of far right political parties are characterized. The role of economy in their ideology is emphasized and main issues, highlighted in the far right parties’ programs, are identified. The essence of social market economy from far right parties’ perspective as well as their views on tax system, welfare etc. are analyzed in details. The term ‘welfare chauvinism’, used to characterize socio-economic program of far right parties, is defined.